2010
DOI: 10.1007/s00359-010-0569-6
|View full text |Cite
|
Sign up to set email alerts
|

Auditory fovea and Doppler shift compensation: adaptations for flutter detection in echolocating bats using CF-FM signals

Abstract: Rhythmical modulations in insect echoes caused by the moving wings of fluttering insects are behaviourally relevant information for bats emitting CF-FM signals with a high duty cycle. Transmitter and receiver of the echolocation system in flutter detecting foragers are especially adapted for the processing of flutter information. The adaptations of the transmitter are indicated by a flutter induced increase in duty cycle, and by Doppler shift compensation (DSC) that keeps the carrier frequency of the insect ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
175
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(180 citation statements)
references
References 121 publications
3
175
1
1
Order By: Relevance
“…These long, narrow-band echolocation signals enable the bats to use echo cues caused by the wing beats of the flying insects upon which they prey. Fluttering insects cause frequency modulations in the returning echoes, which contain the information necessary for the bat to detect and even recognize its prey (27,28).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These long, narrow-band echolocation signals enable the bats to use echo cues caused by the wing beats of the flying insects upon which they prey. Fluttering insects cause frequency modulations in the returning echoes, which contain the information necessary for the bat to detect and even recognize its prey (27,28).…”
Section: Resultsmentioning
confidence: 99%
“…A filter mechanism that is narrowly tuned to the echo's narrowband frequency component rejects background clutter while it helps to detect acoustic glints. This auditory filter is found in the cochlea, and results in an increased number of receptor cells in the cochlea as well as higher-order auditory neurons that are highly sensitive to the echo pure tone (27,37). Because in the mammalian eye and within the visual central nervous structures the area of the optic fovea is overrepresented in a very similar manner, the auditory filter in horseshoe bats is similarly called an "auditory fovea" (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…the CF of the second harmonic of the echo-locating signal, are highly overrepresented [35,52,60], as well as Doppler shift compensation (DSC) that maintain the CF component of echoes within the sensitive auditory fovea [118,119]. Behavioral studies have showed that mustached bats and some horseshoe bats are adept at attacking fluttering targets [120,121], which induce the echo to generate frequency and amplitude shifts called glints [117,122], but the echo duration does not change and becomes a "tag" recognizing the echo from the target [61].…”
Section: Translational Neurosciencementioning
confidence: 99%
“…For the first paper of this section, Schnitzler and Denzinger (2011), as already mentioned above, reviewed the discovery and investigation of the auditory fovea and of Doppler shift compensation. Borina et al (2011) found a population of auditory midbrain neurons that are sensitive to interaural time differences of the echo envelope and suggest that, in addition to interaural intensity differences, interaural time differences are used for object location by echolocating bats.…”
mentioning
confidence: 99%